(untitled) (American Journal of Islam and Society, 2010)
One cannot think of politicized Islam in Iran without thinking of the Iranian Left’s formation and overall history. The awkward yet symbiotic relationship between them continues to impact how political decisions are made, especially at the parliamentary level. Given the Left’s wide-ranging linkages with surrounding regions, including the Causacus (early twentieth century) and the Arab Middle East (particularly during the 1970s), experts dealing with those regions’ politics would benefit from this work. As one of the Middle East’s strongest leftist movements before the 1980s, any discussion of neighboring revolutionary movements must at least consider it. Although this book assumes familiarity with twentieth-century Iran’s secular politics and might be considered too dense, its rather large bibliographic section is meant to encourage individual intellectual pursuits. Many contemporary scholars of the Iranian Left agree on its adherents’ general lack of critical self-reflection throughout the twentieth century. Reformers and Revolutionaries in Modern Iran offers a forum for critical reassessments of organizational platforms along with constructive propositions meant to enhance the viability of left-leaning programs – especially social-democratic initiatives. This latter point is crucial, because several contributors deliberately state the importance of rejuvenating the Left through social democratic reformism. Historical examples are used to prove this option’s viability over the more “rigid” Marxist-Leninist and Stalinist examples ...